Investigation of the effects of sewing threads on the sewing performance - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2014)
The quality of the fabric is not the only parameter for the production of a high quality cloth. The conversion of two dimensional fabric into the three dimension is related to some parameters such as: selection the proper sewing thread, optimization the sewing parameters, conveniences in the cloth manufacturing process, and the cloth usage performance. These parameters also compose the basic data which are necessary for the analysis of fabric sewable characteristics. The sewing performance is one of the factors that affect the sewability of the fabric which is used in manufacturing process. The aim of this study is to investigate the sewing performances of PBT, PES/cotton core-spun and mercerized cotton sewing threads in a comparative way. For this purpose four different variables (stitch type, seam density, sewing thread type and sewing needle type) were used with the poplin and gabardine fabrics to obtain the optimum seam performance. After sewing process each combination was tested in Instron 4411 instrument and the test results were compared on behalf of the sewing thread type.
Keywords: sewing performance; PBT; core-spun; sewing thread